Foreign experience in the implementation of publicprivate partnership projects in the field of health and education - Fail Ibyatov (Управление)
Public-private partnership acts as a form of effective interaction between the public partner and private investors in order to solve various social problems. The social sphere, being mainly the object of direct public administration and financing, is experiencing significant needs in resources, the introduction of modern management methods and advanced technologies. Budget funds do not allow to fully and in a short period to solve these problems, so it becomes necessary to attract directly the competencies and investments of the private sector. Education and health are at the center of the social sectors. The relevance of the use of public-private partnership in the social sphere is due to the fact that in a relatively short period of time it is possible to eliminate gaps in the development of social infrastructure by combining efforts, funds, risks of two economic entities – the state and business. The study of foreign experience in the implementation of socially significant projects using public-private partnership tools is necessary to assess the possibility of using similar models in Russia. Interaction between the state authorities and the private sector in terms of pooling resources and potentials within this task will actively attract investment, efficiently and timely implement social projects, improve the quality of social services to the population, increase the level of management of social infrastructure, promote the development of public institutions of the social sphere. At the same time, the public-private partnership will help to use effectively financial resources, experience and professionalism of the private sector while maintaining state control over social assets. Based on the analysis of the uncovered need for resources for the accelerated development of the social sphere, the author of the article proposes: the launch of new mechanisms of financial support from the Federal budget and the increase in budget funding for the purpose of providing “budget leverage” in public-private partnership projects; improvement of legislation in the field of public-private partnership to eliminate “barriers” and simplify the procedure for launching public-private partnership projects in education and health care; updating planning documents (changing existing documents of state strategic planning), including with a view to change priorities in infrastructure development and the mechanisms used for this.